Analisis Ketersediaan Dan Kebutuhan Beras di Provinsi Sumatera Utara - Sari, Yunita; Lubis, Zulkarnain; Khardinata, E. Harso (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This study aims to determine and analyze the availability and need of rice in North Sumatra Province and determine the factors that influence it. This type of research is a quantitative analysis using coherent secondary data from 2008-2017 in 33 districts / cities in North Sumatra Province. The data analysis technique used is Descriptive Analysis. To test the factors that influence the availability and need of rice in North Sumatra Province, multiple linear regression analysis is used and to determine the causal relationship between variables, we use Causal Relations Analysis. The results showed that rice production in North Sumatra Province was fluctuating in 2008-2017 and tended to increase by an average of 4.79 percent per year. The availability of this rice comes from local production and has met the needs of the community. This is indicated by the condition of the rice surplus in North Sumatra Province in 2017 which amounted to 1,065,886 tons. The availability of rice in North Sumatra Province on average has increased 5.27 percent per year. Based on the results of the study note that the rice production variable has a positive and significant effect on the availability of rice in North Sumatra Province, while other variables namely the rice harvest area variable and the need for rice consumption have no significant effect. GRDP income variable and rice availability variable significantly influence rice needs in North Sumatra Province, while the population number variable does not significantly influence rice demand.